Nocebo Effects of Clinical Communication and Placebo Effects of Positive Suggestions on Respiratory Muscle Strength - Zech, Nina; Scharl, Leoni; Seemann, Milena; Pfeifer, Michael; Hansen, Ernil (Frontiers in Psychology, 2022)
Introduction: Nocebo effects usually are studied by parameters specific for the tested suggestion. We recently proposed the use of a uniform, unrelated and objective measure like maximal muscle strength that allows comparison of suggestions to improve communication. Since reduced breathing strength might impair respiration and increase the risk of postoperative pulmonary complications, the aim of the present study was to evaluate suggestions effects on respiratory muscle power. Both, identification, and neutralization of negative suggestions in the clinical context and stimulating suggestions could improve breathing force. Methods: In 50 healthy volunteers, respiratory muscle strength was measured by the maximal inspiratory and expiratory pressures, as well as by the maximal inspiratory and expiratory flows. Baseline was compared to values after application of eleven suggestions, five out of clinical context including memory of negative or positive past, risk information for informed consent and a nonverbal suggestion. Six stimulating suggestions included self-affirmation, empowering words, a heroic mirror image, and an imagination. Results: All suggestions showed impact on respiratory muscle strength indicating placebo and nocebo effects. No single parameter could represent breathing force in its complexity, however trends and different specific aspects of it were measured. The strongest reaction was observed with the recall of a past negative situation resulting in a reduction of expiratory flow to 96.1% of baseline. After risk information a decrease was seen in three of the parameters, with the highest extend in expiratory pressure by 4.4%. This nocebo effect was neutralized with adding positive aspects to the risk information. Every intended strengthening suggestion resulted in a statistically significant increases of at least one parameter, with changes up to 10%. Here, expiration was more affected than inspiration. Gender was the only influencing factor reaching statistical significance, with stronger reactions in women. Conclusion: Respiratory muscle strength proved to be sensitive to suggestions with clinical context as well as suggestions intended for stimulation. With respiratory flow and pressure parameters, an objective measurement, evaluation, and comparison of different suggestions was possible. Breathing force is a clinically relevant parameter which obviously can be supported by use of suggestions.